Optimising Nanoparticle Dispersion Time for Enhanced Thermomechanical Properties in DGEBA-Based Shape Memory Polymer Composites - Jeewantha, Janitha; Epaarachchi, Jayantha; Islam, Md Mainul (Journal of Research Updates in Polymer Science, 2024)
Shape-memory polymers (SMPs) are smart materials that can change shape upon an external stimulus. This phenomenon is called the shape memory effect (SME), which is caused by entropy change due to rapid molecular motion in the polymer segments. Due to the inherently weak thermomechanical properties, use of SMPs is limited in many engineering applications. Therefore, SMPs are often reinforced with fibres and nanoparticles (NPs). NPs offered greater flexibility due to their superior physical, chemical, electrical, mechanical, and thermal properties. However, the homogeneous distribution of NPs is crucial for composition’s stability and enhancement of the base material’s properties. Among the different techniques used for dispersing NPs, ultrasonic irradiation has shown excellent emulsifying and crushing performance. The sonication process is essential for mitigating agglomerates; however, prolonged sonication time probably increases epoxy temperature, micro-bubbles, cavitation, breaking apart molecules and finally degrading the epoxy resin performances. This paper provides critical insight of nanoparticle dispersion into diglycidyl ether of bisphenol A epoxies (DGEBA). DGEBA epoxy resin was added to TiO2 NPs and sonicated for 60 min with 5 min intervals while the temperature of epoxy was maintained below 60oC by using a water cooling throughout the sonication process. The process parameters such as amplitude, mode, epoxy volume and the weight percentage of NPs were kept constant. After each sonication step, Fourier-transform infrared spectroscopy (FTIR) was performed using Thermo Scientific™ and analysed through OMNIC™ Professional quantitation software. In accordance with FTIR results, until 30 min of the sonication, DGEBA resin was not degraded. In order to confirm the performances and the reinforcing effect of NPs, thermo-mechanical and shape memory properties were compared with the neat specimen. The outcomes of this research have suggested quick guidance to find optimum NP dispersion time for DGEBA resins, which has been hardly studied before.